Optical and surface enhanced Raman scattering properties of Au nanoparticles embedded in and located on a carbonaceous matrix - Prakash, Jai; Kumar, Vinod; Kroon, R. E; Asokan, K; Rigato, V; Chae, K. H; Gautam, S; Swart, H. C (Physical Chemistry Chemical Physics, 2016)
Au nanoparticles (NPs) on the surface and embedded in a matrix have been the subject of studies dealing with a variety of spectroscopic and sensing applications. Here, we report on low energy Ar ion induced evolution of the morphology of a thin Au film on a polyethylene terephthalate (PET) substrate along with thermodynamic interpretations, and corresponding unique surface plasmon resonance (SPR) and photoluminescence (PL) properties. These properties are linked to the variation of surface nanostructures and the surface enhanced Raman scattering (SERS) effect of methyl orange (MO) dye molecules adsorbed on the surface. Ion induced thermal spike and sputtering resulted in dewetting of the film with subsequent formation of spherical NPs. This was followed by embedding of the NPs in the modified PET due to the thermodynamic driving forces involved. The surface and interface morphologies were studied using atomic force microscopy and cross-sectional transmission electron microscopy. X-ray photoelectron spectroscopy was used to study the chemical changes in the system upon irradiation. The optical properties were studied by diffuse reflectance UV-Vis spectroscopy and PL using a 325 nm He-Cd laser. The red shift of the SPR absorption and the blue shift of the PL emission have been correlated with the surface morphology. The blue PL emission bands at around 3.0 eV are in good agreement with the literature with respect to the morphological changes and the blue shift is attributed to compressive strain on the embedded Au NPs. Enhancement of the SERS signals is observed and found to be correlated with the SPR response of the Au nanostructures. The SERS analyses indicate that MO molecules may be adsorbed with different orientations on these surfaces i.e. Au NPs located on the surface or embedded in the modified PET. These polymeric substrates modified by NPs can have a potential application in solid-state light emitting devices and can be applied in SERS based sensors for the detection of organic compounds. Au nanoparticles (NPs) on the surface and embedded in a matrix have been the subject of studies dealing with a variety of spectroscopic and sensing applications.